Mutiple curved crack problems in antiplane elasticity for circular region with traction free boundary - Dahalan, Noraini; Nik Long, Nik Mohd Asri; Eshkuvatov, Zainidin K. (Universiti Putra Malaysia Press, 2013)
The multiple curved cracks in a circular region problem in antiplane elasticity is formulated in terms of hypersingular integral equation in conjunction with the complex variable function method. The obtained hypersingular integral equations are solved numerically using the curve length coordinate method, where the curved crack configurations are mapped on the real axes s with intervals( , ) 1, 2,..., . i i − = a a n . Suitable scheme is used for the determination of the unknown functions. For numerical purposes only a particular case of doubly circular arc cracks is considered, and it is found that the stress intensity factors (SIFs) are higher as the cracks become closer to the circular boundary.